The Effect Of Loneliness At Work Intention To Leave With Resilience As A Moderating Variable Study At Bank X In Jakarta - Andreas Sidol; Martinus Parnawa Putranta (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the effect of loneliness at work on intention to leave with resilience as a moderating variable. The study was conducted on back office employees at Bank X, Jakarta, using a quantitative approach. Data were collected through questionnaires from 120 respondents and analyzed using Partial Least Square (PLS). The results showed that loneliness at work has a positive influence on intention to leave. Resilience is proven to moderate the relationship between loneliness at work and intention to leave, where individuals with high levels of resilience tend to be better able to deal with the negative impact of loneliness at work. This research is expected to provide theoretical contributions to the organizational psychology literature as well as practical implications for managing human resources, especially in reducing turnover rates.